On the Asymmetric Effects of Exchange Rate Volatility on Trade Flows: Evidence from Africa. Issue 4 (15th March 2020) - Bahmani-Oskooee, Mohsen; Arize, Augustine C.
ABSTRACT: A glance through the literature on the effects of exchange rate uncertainty on the trade flows reveals that African countries have received the least attention. We consider the response of exports and imports of 13 African nations to a Generalized Autoregressive Conditional Heteroskedasticity (GARCH)-based measure of exchange rate uncertainty. Like previous research, when we used linear models in which the effects are assumed to be symmetric, we found significant long-run effects in almost one-third of the countries in our sample. However, when we shifted to nonlinear export and import demand models, we found significant long-run effects of exchange rate uncertainty on trade flows of almost all countries. These effects were asymmetric in nature.